Generalized anxiety therapy and socialization therapy to overcome social anxiety in junior high school adolescents - Surahman, Alissa Puspita; Windarwati, Heni Dwi; Nova, Renny (PT Saintek Medika Nusantara, 2021)
Social anxiety on adolescents is a condition when adolescents feel anxious due to internal or external pressure, thus causing them prone to experience anxiety when they were in a social situation. Generalized anxiety therapy as a non-pharmacological therapy is used to reduce anxiety in adolescents, while socialization therapy is used to increase their ability to socialize, one of which is to communicate with same-age friends. This study aimed to analyze the effect of giving generalized anxiety therapy and socialization therapy on the level of social anxiety in junior high school students in Malang. This study used a quasi-experimental design with a non-randomized pretest-posttest control group design. The number of 60 participants was divided into two groups: the experimental group and the control group. This study has shown no significant decrease in social anxiety levels from giving generalized anxiety therapy and socialization therapy in both groups. This study showed no significant difference in giving generalized anxiety therapy and socialization therapy for social anxiety in adolescents. However, generalized anxiety therapy and socialization therapy may be an alternative to non-pharmacological therapy in adolescents with social anxiety, but it needs more research about this topic to improve evidence-based practice.